Ghana : projected level of demand, supply and imports of agricultural products in 1965, 1970 and 1975 - Ord, H. W. (Washington, D.C. : Economic Research Service, Foreign Agricultural Service, U.S. Dept. of Agriculture, 1964)
This report was prepared for the Economic Research Service and the Foreign Agricultural service of the United States Department of Agriculture under contract with the Department of Political Economy, University of Edinburgh, Scotland
Cover title.
Director of project: H. W. Ord.
Includes bibliographical references.
osc 31/01/2019
Ref
Keywords: Produce trade; Food industry and trade